Research Progress on the Corrosive Environment Large-Scale Evolution for Nuclear Waste Container - Zhang, Qichao; Jiang, Yishan; Zhao, Xin; Chen, Juna; Xia, Dahai; Zhang, Binbin; Duan, Jizhou (Frontiers in Materials, 2022)
After the nuclear waste container buried underground 500-1000 m, it gradually experiences the dual effects of groundwater infiltration and the decay heat of radioactive nuclear waste. The decay and heat release of nuclear wast will also result in the temperature stress. At the same time, the groundwater will gradually saturate the buffer / backfill materials which will produce expansion stress, thus forming a typical thermal-water-stress multi-coupling environment in the geological disposal, forming the environment where the corrosion could happen. In comparison, the information obtained through laboratory, field test and natural simulation are limited. However, numerical simulation is very important to predict the changes of near-field environment. On the one hand, the numerical simulation can verify the corresponding experimental data in the early stage, on the other hand, it can also predict the long-term corrosion environment change. This paper mainly summarizes the large-scale evolution of typical corrosion environment obtained by numerical simulation under different deep geological conditions in various countries, focusing on the effects of temperature, saturation, oxygen content and radiation, which provides a reference for the research on the evolution of important corrosion environment on the surface of nuclear waste container.